Audit Tenure, Audit Fee, and Audit Quality : Evidence from India - Ramesh, Latha; Kamath, Rajashree (Indian Journal of Finance, 2022)
This paper examined the relationship between the tenure of the auditor and the audit quality of Indian companies, particularly in the wake of two significant regulations in the financial reporting, the implementation of Ind AS (the IFRS compliant accounting standards) and mandatory auditor rotation. Using Discretionary Accruals as a proxy for audit quality, the study took the data of all the companies listed on the NSE for 11 financial years, from 2009 – 2019 (totaling 8,171 firm-year observations). It deployed panel data regression with a random-effects model. The results showed that audit quality improved up to specific auditors’ tenure, particularly with the IFRS compliance and Big 4 auditors. The higher audit fee is positively significantly associated with lower earnings quality. The study suggested that mandatory auditor rotation might provide the full benefit only along with other regulations on IFRS, auditor reputation, and audit fee. The study provided an impetus to the regulators, audit fraternity, and companies to improve the relevance of financial statements. This is one of the first longitudinal studies examining the interaction effects of different audit regulations. Robustness checks with other proxies of audit quality provided the same results.